Marketing information products and services : a primer for librarians and information professionals - Jain, Abhinandan K.; International Development Research Centre (Canada) (New Delhi ; New York : Tata McGraw-Hill Pub. Co., 1999)
Contributed articles presented at a workshop held in 1994.
"International Development Research Centre."
Includes bibliographical references.
Keywords: Libraries -- Public relations -- India; Information services -- India -- Marketing; Information services -- Public relations -- India; Marketing research